use a direct proof to show that every odd integer is the difference of two squares. i dont understand how the solution defines ((k+1)^2)-(k^2) = n from (n = 2K+1) where does the (k+1)^2 and the k^2 come from?
Follow Math Help Forum on Facebook and Google+
Originally Posted by camboguy use a direct proof to show that every odd integer is the difference of two squares. i dont understand how the solution defines ((k+1)^2)-(k^2) = n from (n = 2K+1) where does the (k+1)^2 and the k^2 come from? $\displaystyle (x+1)^2=x^2+2x+1$
View Tag Cloud